To simplify the expression \( 12(9 - 70) + (-29)0 \), let's break it down step by step:
-
Calculate \( (-29)0 \):
- Any number multiplied by zero equals zero, so \( (-29)0 = 0 \).
-
Simplify the expression: \[ 12(9 - 70) + 0 = 12(9 - 70). \]
-
Now calculate \( 9 - 70 \): \[ 9 - 70 = -61. \]
-
Substitute back into the expression: \[ 12(-61) = -732. \]
Now let's examine each of the given response options to find one that is equal to \(-732\).
-
First option: \( 12(9 - 1) + 1 \)
- \( 9 - 1 = 8 \)
- \( 12(8) + 1 = 96 + 1 = 97 \) (not equal to -732)
-
Second option: \( \frac{1}{2}(9 - 1) + 1 \)
- \( 9 - 1 = 8 \)
- \( \frac{1}{2}(8) + 1 = 4 + 1 = 5 \) (not equal to -732)
-
Third option: \( 12(9 - 0) + 0 \)
- \( 9 - 0 = 9 \)
- \( 12(9) + 0 = 108 + 0 = 108 \) (not equal to -732)
-
Fourth option: \( 12(2) + \frac{1}{2}(2) + 1 \)
- \( 12(2) = 24 \)
- \( \frac{1}{2}(2) = 1 \)
- \( 24 + 1 + 1 = 26 \) (not equal to -732)
-
Fifth option: \( 12(9 - 1) - 1 \)
- \( 9 - 1 = 8 \)
- \( 12(8) - 1 = 96 - 1 = 95 \) (not equal to -732)
None of the provided responses are equal to \(-732\). Please verify the equation you provided or check if there are additional response options.